Confronting the challenge of reproductive health in Africa : a textbook for students and development practitioners - Okonofua, Friday.(ed.) (Florida Brown walker Press, 2014)
Confronting the Challenge of Reproductive Health in Africa is an indispensable resource for anyone delving into the field of sexual and reproductive health and rights, either as a student, practitioner or policymaker. The compilation of chapters provides contemporary and detailed information about the context, principles and practice of reproductive health in Africa from multidisciplinary and multi-sectorial perspectives, as well as evidence for designing cost-effective interventions. Written in a simple free flowing prose by experienced international scholars, and organized in an orderly manner, the book will fill an important gap in health promotion for development in Africa.--
Keywords: Reproductive Health. -- Africa; Family planning -- Africa; Sex instruction -- Africa; Mothers mortality